Brief Report: Yield of Repeat Tuberculin Skin Testing for People Living With HIV in Brazil. (1st December 2021) - Chaisson, Lelia H.; Saraceni, Valeria; Cohn, Silvia; Cavalcante, Solange C.; Chaisson, Richard E.; Durovni, Betina; Golub, Jonathan E.
Abstract : Objectives: In Brazil, annual tuberculin skin tests (TSTs) are recommended for people living with HIV (PLWH) with CD4 >350, with tuberculosis preventive therapy provided on test conversion. We aimed to determine the yield of repeat TSTs for PLWH. Design: Secondary analysis of the stepped-wedge, cluster-randomized THRio trial for isoniazid preventive therapy (IPT) to prevent tuberculosis (TB). Methods: We analyzed data from newly registered PLWH with negative baseline TST results. We calculated the number of TST conversions after 1 and/or 2 years among patients eligible for follow-up TSTs, the proportion of converters initiating IPT, and incidence of TB/death. Results: Among 1770 PLWH with a negative baseline TST, 679 (38%) were female and median age was 36 years (IQR 29–43). Eighty-six (5%) developed TB or died within 1 year. Among 1684 eligible for a follow-up 1-year TST, 582 (35%) were tested and 53 (9%) were positive. Forty-nine converters (92%) started IPT. Of 529 patients with a negative 1-year TST, 7 (1%) developed TB or died over the following year. Of 522 patients eligible for a 2-year TST, 158 (30%) were tested and 13 (8%) were positive. Ten converters (77%) started IPT. Of 1102 patients who did not receive a 1-year TST, 33 (3%) developed TB or died. Of the 1069 patients eligible for a 2-year TST, 259 (24%) were tested and 34 (13%) were positive. Thirty converters (88%) started IPT. Conclusions: In this cohort of PLWH in Brazil, TST conversion was high among those retested, but only 48% received a follow-up TST within 2 years.